Identifikasi Ruang Terbuka Hijau (RTH) Publik di Kawasan Pusat Kota Kepanjen Kabupaten Malang - Rahma, Pamela Dinar ; Supriyanti, Dipa (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2018)
Kepanjen as the capital of Malang Regency continues to improve, in addition to being equipped with various public facilities and green open spaces, it will also be used as a pilot as a green city by the Regency Government. Currently Kepanjen City already has several public green open spaces, but the existing public open green space still does not meet the standard area of ??green open space of a region. Therefore this study will evaluate the availability of public green open space in Kepanjen City. This study aims to find out the distribution of public green open space in the Kepanjen City Center. The method used in this study is evaluative descriptive, how to obtain data by field observations, interviews and recording. Based on the results of the survey and analysis that the public green open space in the Kepanjen City Center Area consists of railroad borders, river borders, cemeteries, and green roads. Railroad green open space along 3 km along the railroad tracks, each river has been protected by green open space river border, in the central area of ??Kepanjen City has two public cemeteries and one Chinese cemetery which also functions as a green open space, and the Green Roadway in Kepanjen urban area is located on Panglima Sudirman street, Kawi, Panji street, Sultan Agung street, and Dr Wahidin Sudirohusodo street.